2018
DOI: 10.1071/an16147
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of meat from triceps brachii muscle from steers and heifers finished on high-concentrate diets containing increasing concentrations of linseed oil

Abstract: The aim of the present study was to assess the qualitative and chemical characteristics of a shoulder muscle (triceps brachii muscle, medial head (TBm)) of 15 Nellore × Canchim steers and 14 heifers of the same cross fed diets containing 80% concentrate on a dry-matter (DM) basis and increasing concentrations of linseed oil (1%, 3.8% and 5.2% of DM). A randomised incomplete-block design, divided on the basis of initial bodyweight, in a 3 × 2 factorial scheme (oil concentration and animal sex) was used. Oil con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, the c 9, t 11-CLA level in the longissimus muscle of bulls in each linseed-supplemented diet was higher than those of the other two groups which were fed on a diet devoid of linseed. Oliveira et al further investigated the effect of the increased inclusion of linseed in the feeding diet on the CLA content of crossbred steers and heifer and found that the increased use of linseed in the diet leads to increased content of CLA in the animals, which was also confirmed by Alberti et al…”
Section: Factors That Affect Cla Content In Muscle Food Productsmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, the c 9, t 11-CLA level in the longissimus muscle of bulls in each linseed-supplemented diet was higher than those of the other two groups which were fed on a diet devoid of linseed. Oliveira et al further investigated the effect of the increased inclusion of linseed in the feeding diet on the CLA content of crossbred steers and heifer and found that the increased use of linseed in the diet leads to increased content of CLA in the animals, which was also confirmed by Alberti et al…”
Section: Factors That Affect Cla Content In Muscle Food Productsmentioning
confidence: 71%
“…In addition, the c9,t11-CLA level in the longissimus muscle of bulls in each linseedsupplemented diet was higher than those of the other two groups which were fed on a diet devoid of linseed. Oliveira et al 107 further investigated the effect of the increased inclusion of linseed in the feeding diet on the CLA content of crossbred steers and heifer and found that the increased use of linseed in the diet leads to increased content of CLA in the animals, which was also confirmed by Alberti et al 10 Safflower seeds, when used as a dietary supplement, can also increase the content of CLA in both muscle and fat tissues of lambs. 99 Compared to the lambs fed without safflower seeds, safflower-seed-supplement-fed lambs had a significant increase in CLA concentration in both their muscle and fat tissues.…”
Section: Factors That Affect Cla Content In Musclementioning
confidence: 76%
“…The concentration of each fatty acid was calculated and divided into classes. They were also classified by functionality as hypocholesterolemic, hypercholesterolemic, neutrals, and residuals, according to Bessa, Lourenço, Portugal and Santos-Silva (2008), Oliveira et al (2017). Thrombogenicity and atherogenicity indices were determined as in Ulbricht and Southage (1991).…”
Section: Methodsmentioning
confidence: 99%